Synthesis and Antimicrobial Activity of Functional Derivatives of thiazolo[ 2,3-c][1,2,4]triazoles - Slivka, Mikhailo; Fizer, Maksym; Mariychuk, Ruslan; Ostafin, Marek; Moyzesh, Olexander; Koval, Galyna; Holovko-Kamoshenkova, Oksana; Rusyn, Ivan; Lendel, Vasyl (Letters in Drug Design & Discovery, 2022)
Background: Condensed triazoles are a well-known class of heterocyclic compounds due to a wide range of biological activities. The study is dedicated to the evaluation of the antimicrobial potential of new functional derivatives of thiazolo[2,3-c][1,2,4]triazoles. Methods: Effective, easy-to-implement and low-cost routes for production of title compounds via electrophilic intramolecular heterocyclization are reported. Bactericidal and fungicidal activities against Gram-positive and Gram-negative bacteria and fungus were studied. The influence of functional groups on the biological activity of tested thiazolo[2,3-c][1,2,4]triazoles is discussed. Results: Microbiological evaluation shows that 6-[(trichlorotellanyl)methyl]-[1,3]thiazolo[2,3- c][1,2,4]triazol-3-amine hydrogen chloride 2a and 3-(2-hydroxyphenyl)-6-[(trichloro-λ4-tellanyl)methyl]- 5,6-dihydro-[1,3]thiazolo[2,3-c][1,2,4]triazole 2g have a high bactericidal activity and Cu (I) salts of 3-(2- hydroxyphenyl)-6-iodomethyl/6-methylidene-5,6-dihydro-[1,3]thiazolo-[2,3-c][1,2,4]triazoles 5a,c have a high fungicidal activity. Conclusion: It is concluded that these products or their derivatives may be of practical benefit as bactericidal and fungicidal agents.
Keywords: tellurium tetrachloride